Analisis Yuridis Kewenangan Absolut Pengadilan Negeri Dalam Memutus Sengketa Gugatan Perbuatan Melanggar Hukum Terhadap Lembaga Pemerintah (Studi Putusan Nomor: 771/PDT.G/2022/PN JKT.PST) - Averoezy, Fauzul; Kartika, Adhitya Widya (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Jurisdiction is one of the most common defenses raised in civil disputes, as it determines whether a case falls within the jurisdiction of the court hearing it. This study is motivated by the discrepancy between legal theory and the practice of law enforcement. The methodology employed is a normative legal approach, utilizing statutory analysis, case law analysis through comparable rulings, and a conceptual analysis regarding jurisdiction, unlawful acts, lawsuits, and government agencies. This study aims to outline the elements of the case, particularly regarding the liability of government agencies for alleged PMH, and to analyze the application of positive law in Indonesia. The results of the study indicate that: (1) the government agency cannot be held liable for PMH because the elements of the alleged provision have not been met; and (2) the panel of judges at the Central Jakarta District Court should have declared that it lacked jurisdiction to hear the case, as jurisdiction lies with the Jakarta Administrative Court.